PENERAPAN MODEL PEMBELAJARAN TIME TOKEN TERHADAP PENINGKATKAN HASIL BELAJAR KONSEP CIRI-CIRI MAKHLUK HIDUP PADA SISWA KELAS VIII SMP KRISTEN YPKPM AMBON - Amelia Popla; Ine Arini (BIOPENDIX, 2019)
Background: Education is a business that is intentionally designed to achieve predetermined goals and provide certain knowledge, insights, skills and expertise to individuals to explore and develop talents and personalities. Method: This study is a descriptive study that describes mastery learning using the Time Token learning model. The sample in this study was class VII2 students consisting of 34 students. Results: This study shows that there is a significant influence by using the time token learning model towards improving student learning outcomes. At the time of the application of the time token learning model, it was seen that student learning outcomes were improved. Data obtained from the research results obtained with an average score reaching 54.70 and being in a failed qualification, while the final test 91.47 is in complete qualification. Conclusion: The application of the time token learning model can improve the learning outcomes of the concept of living things in class VII2 YPKPM Christian Middle School Ambon by showing a significant success rate for students.